PERANAN DINAS PARIWISATA DAN KEBUDAYAAN DALAM MENGEMBANGKAN OBJEK WISATA AIR PANAS SUAMAN DI KABUPATEN ROKAN HULU - Hariani, Solihati; Seprini, Seprini; Afrizal, Andi (Gapenas Publisher, 2025)
This study aims to determine the role of the Tourism and Culture Office in developing the Suaman Hot Springs tourist attraction in Rokan Hulu Regency and identify the obstacles encountered in the development process. The Suaman Hot Springs tourist attraction is a natural tourist attraction with significant potential but has not been optimally managed, particularly in terms of facilities, accessibility, and promotion. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Informants included officials from the tourism office, tourism managers, and visitors. The results indicate that the Tourism and Culture Office has carried out its role in planning, development, policy formulation, and supervision of tourist attraction management. However, budget constraints, inadequate infrastructure, and low community participation are the main obstacles to the development of this tourist attraction. Therefore, cross-sectoral collaboration and community empowerment are needed to improve the quality and competitiveness of the Suaman Hot Springs tourist attraction in a sustainable manner.